Danese Cataneo, «felicissimo spirito» nelle carte tassiane. L’Amor di Marfisa e la Gerusalemme liberata - Artico, Tancredi (Italianistica Debreceniensis, 2017)
Published in 1562, Danese Cataneo’s epic-chivalric poem Amor di Marfisa had a wide but undervalued influence in Torquato Tasso’s masterpiece, Gerusalemme liberata. In this short essay I’ll provide the necessary evidences to demonstrate the existence of a deep connection between those two poems, and establish how it is organized. In particular, Cataneo’s literary legacy, which is underlined by a long list of quote, is strongly perceptible for what concerns the expression of feelings and thoughts. Amor di Marfisa, in this regard, gives to the young Tasso an unusual example of epic poem interested in characters’ psychology: aspects such as the self-analysis and the fragmentation of the ego are underrated in Ariosto’s Orlando furioso and all the other Italian poems in ottava rima, whereas they are fundamental in Cataneo’s poem. More than just an example, it represents for Tasso a training ground and a mine, where he founds themes and lexicon that later will be used in Gerusalemme liberata.